2023
DOI: 10.1021/jacs.2c12163
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to 2-Substituted Bicyclo[1.1.1]pentanes

Abstract: The replacement of aryl rings with saturated carbocyclic structures has garnered significant interest in drug discovery due to the potential for improved pharmacokinetic properties upon substitution. In particular, 1,3-difunctionalized bicyclo[1.1.1]pentanes (BCPs) have been widely adopted as bioisosteres for parasubstituted arene rings, appearing in a number of lead pharmaceutical candidates. However, despite the pharmaceutical value of 2-substituted BCPs as replacements for ortho- or meta-substituted arene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…This substitution pattern stands as a complement to existing methods for preparing 1,2,3-and 1,2,3,4decorated BCP scaffolds. 2,44 The cycloaddition/scaffold-hop sequence reported here can also be performed on gram scale as exemplified for BCP 22. Accordingly, preparation of and subsequent [2+2] photocycloaddition of N-allyl enamide to date.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This substitution pattern stands as a complement to existing methods for preparing 1,2,3-and 1,2,3,4decorated BCP scaffolds. 2,44 The cycloaddition/scaffold-hop sequence reported here can also be performed on gram scale as exemplified for BCP 22. Accordingly, preparation of and subsequent [2+2] photocycloaddition of N-allyl enamide to date.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, 1,2-functionalized BCPs-long sought-after isosteres for ortho-or meta-substituted arenes-have also been prepared by Baran/Pfizer 42 and Ma 43 in an analogous fashion from prefunctionalized [1.1.1]-propellanes. In addition, MacMillan 44 and coworkers reported that radical 2-bromination of the BCP core and subsequent cross-coupling provides access to 1,2,3-substituted variants. In a conceptually distinct strategy, Qin and collaborators at Merck showcased the use of cyclobutyl sulfonylhydrazones in a Barluenga/Valdes-type intramolecular coupling with pinacol boronates to furnish functionalized BCPs.…”
Section: Introductionmentioning
confidence: 99%
“…Deprotection yielded free amine 38 which, following nitrogen deletion, afforded the unique 1,2,4-carbon-substituted BCP 39 in 25% yield (Scheme B). This substitution pattern stands as a complement to existing methods for preparing 1,2,3- and 1,2,3,4-decorated BCP scaffolds. , …”
mentioning
confidence: 99%
“…While BCPs with bridgehead-bound heterocycles are well-known and can be accessed through ATRA, cross-coupling, annulative, and Minisci-type processes, BCPs with heterocycles at the bridge position are rare and represent a potentially valuable yet highly underexplored area of chemical space. , Although a Minisci disconnection to these structures is particularly appealing due to the lack of a requirement for prefunctionalization of the heterocycle, controlled radical transformations at BCP bridge positions are still in their infancy. , The strain energy of the parent BCP hydrocarbon is more than twice that of cyclopropane and cyclobutane, so direct extension of methodologies compatible with these more familiar motifs cannot be guaranteed. Recent evidence has shown that successful application of existing radical-based methodologies to the BCP core often requires significant reaction reoptimization . Herein, we report the direct Minisci-type reaction of free BCP bridge carboxylic acids under hypervalent iodine activation.…”
mentioning
confidence: 99%
“…We highlight that this maximum yield is commensurate with other Minisci reactions reported in the literature , and is acceptable given that the methodology enables direct fragment coupling without a requirement for prefunctionalization/preactivation of either component. The operational simplicity of the reaction renders it suitable for parallel synthesis toward rapid library generation, and unreacted starting materials can be readily recovered from reaction mixtures through a combination of basic aqueous workup and chromatography. Finally, to further contextualize the reaction yield, the attempted synthesis of 9a through Baran’s Negishi cross-coupling provided only traces of the desired product by LCMS analysis in our hands (Scheme ).…”
mentioning
confidence: 99%